The role of urban transport corridors in the formation of agglomerations - A. G. Levashev (Vestnik MGSU)
Introduction. Successful economic and social development of urban territories requires a sustainable transport system that provides reliable connections between territories and a high level of their transport accessibility for the daily social and economic activities of the population. The most important elements of the transport and planning framework of the agglomeration are linear objects, represented by transport corridors, which determine the bulk of transport costs for population movements, and hence transport accessibility of territories. A high level of transport service in such important elements as transport corridors directly affects the formation of sustainable daily migrations of the population and the development potential of the adjacent territories, and therefore affects the formation of the agglomeration boundaries.Materials and methods. For the territory of Irkutsk agglomeration, which includes Irkutsk city as the main core of agglomeration, satellite cities Angarsk and Shelekhov and the surrounding territory of Irkutsk district, approaches to the formation of a unified transport model of agglomeration as the main tool for assessing transport demand, analyzing the distribution of traffic flows and indicators of the effectiveness of measures to develop the territories of transport corridors and the territories served by them are proposed. The paper considers special cases of the constituent parts of the models for assessing transport demand for movements between individual municipalities. An approach to estimating transport demand on adjacent conjugate transport corridors, previously used only for individual corridors is proposed.Results. The significance indicators of transport corridors, including the volume of transport work in relation to their total length were obtained. The example of the application of transport model of Irkutsk agglomeration to solve the problems of the formation of new transport corridors is presented.Conclusions. It is concluded that the proposed approaches to the formation of the transport model allow to prepare the necessary tools in conditions of limited opportunities for mass surveys, as well as maximize the use of existing transport models developed earlier for individual municipalities and transport corridors, combining them into a single transport model.